Going green? How skepticism and information transparency influence consumers' brand evaluations for familiar and unfamiliar brands. Issue 1 (19th June 2020) - Bhaduri, Gargi; Copeland, Lauren
Abstract : Purpose: To help brands persuasively communicate their environmentally responsible initiatives, this study aims to involve two experiments, examining the impact of brand schema, information transparency and skepticism toward climate change for brands both familiar and unfamiliar to US consumers. Design/methodology/approach: Two online experiments were designed recruiting a total of 510 participants. The design incorporates both message and treatment variance to increase internal and external validity of the study. Data collected were analyzed using PROCESS, a regression-based conditional path analysis technique. Findings: The results indicated that for both familiar and unfamiliar brands, increased congruity of consumers' schemas to information presented in brands' pro-environmental messages led consumers to evaluate the messages as more persuasive, have more positive opinions about brands' environmentally responsible initiatives as well as behavioral intentions toward the brand. Also, presence of high information transparency on environmental responsibility-related messages influenced consumers' schemas positively, and in turn, their evaluations were more favorable. However, consumers' climate change skepticism seemed to influence unfamiliar, not familiar brands. Originality/value: The study provides both theoretical and managerial implications. The findings are important for established apparel brands that suffer from negative reputations, but are willing to revitalize their images, and for new ventures who want to establish their image as environmentally responsible.